2007
DOI: 10.1007/s00383-007-2019-2
|View full text |Cite
|
Sign up to set email alerts
|

Anterior sagittal anorectoplasty for anovestibular fistula

Abstract: Anterior sagittal anorectoplasty (ASARP) was used for the definitive correction in 107 cases of anovestibular fistula (AVF) between 1996 and 2005. These cases were subjected to three different types of treatment regimes during the same period. Majority of the cases (78) were operated in one stage where postoperatively an early oral feed was started (A). Cases were discharged in 2-4 days. In the second group (B), there were ten cases who were also operated in one stage but with prolonged fasting of 9-10 days po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 16 publications
(32 reference statements)
4
35
0
Order By: Relevance
“…(8,9) Various surgeons have reported that there is no significant difference in multistage and single stage procedure. (10)(11)(12)(13)(14)(15)(16)(17) Our series is small for statistical analysis, but the results are in accordance with these reported series outcome in terms of continence can be achieved by careful anterior sagittal surgical dissection. Anovestibular fistula can be repaired in one stage with meticulous pre-and postoperative bowel management.…”
Section: Discussionsupporting
confidence: 79%
“…(8,9) Various surgeons have reported that there is no significant difference in multistage and single stage procedure. (10)(11)(12)(13)(14)(15)(16)(17) Our series is small for statistical analysis, but the results are in accordance with these reported series outcome in terms of continence can be achieved by careful anterior sagittal surgical dissection. Anovestibular fistula can be repaired in one stage with meticulous pre-and postoperative bowel management.…”
Section: Discussionsupporting
confidence: 79%
“…The surgical management is warranted after the colostomy. Posterior sagittal anorectoplasty (PSARP) is performed as a choice [5][6][7]. There is always fear of stool incontinence because of the anal sphincter problems.…”
Section: Discussionmentioning
confidence: 99%
“…Other advantage of this approach is that it can be done under caudal anesthesia. Okada 3 and Sanchez 4 have recommended prolonged fasting and TPN; however it requires prolonged hospitalization and has poor patient tolerance and passage of hard stool which may harm suture line 5 . We agree with Whaklu et al 6 in…”
Section: Discussionmentioning
confidence: 99%